Clinical presentations and outcomes of patients with Ebola virus disease in Freetown, Sierra Leone. Issue 1 (December 2016) - Ji, Ying-Jie; Duan, Xue-Zhang; Gao, Xu-Dong; Li, Lei; Li, Chen; Ji, Dong; Li, Wen-Gang; Wang, Li-Fu; Meng, Yu-Hua; Yang, Xiao; Ling, Bin-Fang; Song, Xue-Ai; et al.
Abstract Background Clinical and laboratory data were collected and analysed from patients with Ebola virus disease (EVD) in Jui Government Hospital in Freetown, Sierra Leone, where patients with EVD were received and/or treated from October 1, 2014 to March 21, 2015 during the West Africa EVD outbreak. Methods The study admitted 285 patients with confirmed EVD and followed them up till the endpoint (recovery or death). EVD was confirmed by quantitative RT-PCR assays detecting blood Ebola virus (EBOV). Results Among the 285 lab-confirmed EVD cases in Jui Government Hospital, 146 recovered and 139 died, with an overall survival rate of 51.23 %. Patients under the age of 6 years had a lower survival rate (37.50 %). Most non-survivors (79.86 %) died within 7 days after admission and the mean hospitalization time for non-survivors was 5.56 ± 6.11 days. More than half survivors (63.69 %) turned blood EBOV negative within 3 weeks after admission and the mean hospitalization time for survivors was 20.38 ± 7.58 days. High blood viral load (≥106 copies/ml) was found to be predictive of the non-survival outcome as indicated by the Receiver Operating Characteristic (ROC) curve analysis. The probability of patients' survival was less than 15 % when blood viral load was greater than 106 copies/ml. Multivariate analyses showed that blood viral load (P = 0.005), confusion (P = 0.010), abdominal pain (P = 0.003), conjunctivitis (P = 0.035), and vomiting (P = 0.004) were factors independently associated with the outcomes of EVD patients. Conclusions Most death occurred within 1 week after admission, and patients at the age of 6 or younger had a lower survival rate. Most surviving patients turned blood EBOV negative within 1–4 weeks after admission. Factors such as high blood viral load, confusion, abdominal pain, vomiting and conjunctivitis were associated with poor prognosis for EVD patients.